2006
DOI: 10.1186/1476-4598-5-1
|View full text |Cite
|
Sign up to set email alerts
|

Stable low-level expression of p21WAF1/CIP1 in A549 human bronchogenic carcinoma cell line-derived clones down-regulates E2F1 mRNA and restores cell proliferation control

Abstract: Background: Deregulated cell cycle progression and loss of proliferation control are key properties of malignant cells. In previous studies, an interactive transcript abundance index (ITAI) comprising three cell cycle control genes, [MYC × E2F1]/p21 accurately distinguished normal from malignant bronchial epithelial cells (BEC), using a cut-off threshold of 7,000. This cut-off is represented by a line with a slope of 7,000 on a bivariate plot of p21 versus [MYC × E2F1], with malignant BEC above the line and no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
35
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(37 citation statements)
references
References 44 publications
2
35
0
Order By: Relevance
“…myo -Inositol and its derivatives have previously been associated with different cancer-types/biological matrices and varying direction of change (Aa et al 2012; Perroud et al 2006; Thysell et al 2010). Denkert et al reported lower levels of an inositol stereoisomer in colon cancer tissue compared to normal colon mucosa (Denkert et al 2008), in concordance with the observed lower urinary myo -inositol levels in pre-surgery, tumor bearing patients in our study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…myo -Inositol and its derivatives have previously been associated with different cancer-types/biological matrices and varying direction of change (Aa et al 2012; Perroud et al 2006; Thysell et al 2010). Denkert et al reported lower levels of an inositol stereoisomer in colon cancer tissue compared to normal colon mucosa (Denkert et al 2008), in concordance with the observed lower urinary myo -inositol levels in pre-surgery, tumor bearing patients in our study.…”
Section: Discussionmentioning
confidence: 99%
“…For GC-MS analysis, the method for urine sample preparation was adapted from literature (Cheng et al 2012), but without urease treatment because low enzyme specificity resulting in distorted metabolite levels have been reported by several research groups (Kind et al 2007; Perroud et al 2006). Pooled quality control (QC) samples and Kovat’s alkane mixtures were injected with each analytical batch.…”
Section: Methodsmentioning
confidence: 99%
“…For example, the Warburg effect represents a shift to increased aerobic glycolysis and increased production of lactate, as well as increased bioenergetic demand [15]. Because some metabolic alterations occur early in the process of neoplastic transformation they may provide not only biomarkers for early detection, but perhaps more importantly, targets for intervention [10,16]. Other alterations include increases in total choline-containing compounds, myo-inositol, taurine, and pyruvate kinase type M2 (glycolytic isoenzyme).…”
Section: Metabolic Characteristics Of Normal and Malignant Prostatementioning
confidence: 99%
“…For instance, Rubin et al [55] showed that a combination of ligands for PPAR γ and RXR inhibits breast aromatase expression induced by tumor-derived factors. Because aromatase activates estrogen biosynthesis, the combination of these ligands may be able to find utility in thetreatment of estrogen-dependent carcinogenesis, such as breast cancer and endometrial cancer [56]. The combination of RXR ligand with ciglitazone also cooperatively inhibits the growth of breast cancer and lung cancer cells by activating the RARE promoter activity and inducing RAR β , which plays a critical role in mediating the growth-inhibitory effects of retinoids in various cancer cells [57].…”
Section: Synergy Between Pparγ Ligands and Retinoids In Cancermentioning
confidence: 99%